Estimation for Solutions of Ill-Posed Cauchy Problems of Differential Equation with Pseudo-Differential Operators (Journal of Computational Mathematics, 1984)
The estimation for solutions for the ill-posed Cauchy problems of the differential equation $\frac{du(t)}{dt}=A(t)u(t)+N(t)u(t),\forall t\in (0,1)$ is discussed, where $A(t)$ is a 2-nd order p.d.o. and $N(t)$ is a uniformly bounded $h-›H$ linear operator. Two estimates of $||u(t)||$ are obtained.